Análisis de la construcción del discurso digital de Jorge Yunda, alcalde de Quito, como herramienta de nueva medición - Pabón Gordon, Alejandro Fitzgerald (2021)
Since the begining of television as a mass media channel leading to the advent of the 21 century digital media, the eloquence and the charisma of candidate was the main tool for construction of political discourse. Today the disruption of the digital technique plays a more important and determining role on the modern democracy than ever before…